2018
DOI: 10.1177/1744259117754298
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and performance analysis of an earth-to-air heat exchanger in a pilot installation

Abstract: Earth-to-air heat exchanger is an efficient complement to the space heating and cooling systems. An earth-to-air heat exchanger system consists of a set of subterranean pipes leading outdoor air to a ventilation room and by collecting geothermal energy saves some energy. This article presents testing of an earth-to-air heat exchanger installation in a residential building in Coimbra (Portugal) during 1 year. An analytical model is developed and verified with data from the system monitoring. Many variables affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 18 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…On the other hand, when direct expansion GHE systems are investigated, fluid temperature profiles are coupled with the pressure, density, and specific heat profile along the pipes, properties all affected by the phase change of refrigerant inside GHE [40,91,92]. Several authors used dimensionless temperature forms like thermal efficiency or effectiveness of the heat exchanger where temperatures T in , T out , and T g are inlet, outlet, and ground temperatures [58,93,107,108]:…”
Section: Performance Indicators For the Evaluation Of Ghesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, when direct expansion GHE systems are investigated, fluid temperature profiles are coupled with the pressure, density, and specific heat profile along the pipes, properties all affected by the phase change of refrigerant inside GHE [40,91,92]. Several authors used dimensionless temperature forms like thermal efficiency or effectiveness of the heat exchanger where temperatures T in , T out , and T g are inlet, outlet, and ground temperatures [58,93,107,108]:…”
Section: Performance Indicators For the Evaluation Of Ghesmentioning
confidence: 99%
“…Qi et al [115] applied the same approach in their study and also defined analogous thermal performance uniformity coefficient. The COP of the EAHE system, expressed as exchanged heat and consumed power, points out the existence of optimum values of pipe diameter, meaning that larger does not always mean the better [107]. The pressure drop was indirectly taken into account during experiments by Agrawal et al [59] by monitoring fan power consumption to express heat exchanger COP.…”
Section: Performance Indicators For the Evaluation Of Ghesmentioning
confidence: 99%
“…The Nusselt number depends on the surface thermal condition of the pipe; it indicates that the flow is laminar or turbulent, related to the Reynolds number [11,12].…”
Section: Sub-soil Temperature Modelmentioning
confidence: 99%
“…The design parameters of the EAHE are important in the ventilation capacity of the EAHE. Several studies [12][13][14][15][16][17][18][19][20][21][22][23][24] have shown that performance of an EAHE depends on several parameters: (i) the temperature decrease occurs during the first meters of EAHE, (ii) the difference in air temperature between the EAHE output and input decreases as the fluid velocity increases, (iii) the greater or the lower the temperature difference of the air at the entrance and the floor, the greater the heat transfer. On the other hand, those parameters that do not have a significant effect on performance are: (i) increasing the fluid velocity decreases the interaction time between soil and air, (ii) the greater the diameter, the greater the flow of air but greater pressure drops, (iii) the ventilation potential is very similar regardless of the material of the tube, (iv) increase the length of the tube after its optimal distance has small influence on the temperature difference.…”
Section: Introductionmentioning
confidence: 99%